2016
DOI: 10.1016/j.jenvman.2016.04.037
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence and removal of antibiotics in ecological and conventional wastewater treatment processes: A field study

Abstract: a b s t r a c tThe occurrence and removal of 19 antibiotics (including four macrolides, eight sulfonamides, three fluoroquinolones, three tetracyclines, and trimethoprim) were investigated in two ecological (constructed wetland (CW) and stabilization pond (SP)) and two conventional wastewater treatment processes (activated sludge (AS) and micro-power biofilm (MP)) in a county of eastern China. All target antibiotics were detected in the influent and effluent samples with detection frequencies of >90%. Clarithr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
43
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 146 publications
(50 citation statements)
references
References 50 publications
3
43
0
2
Order By: Relevance
“…Among the major point sources of environmental contamination from antibiotics are the UWTPs known for their low efficiency in removing such contaminants by the CAS process. 17 For example, Lindberg et al 18 reported that ciprofloxacin is not readily biodegradable in wastewater during CAS treatment and that 70% of its total amount is adsorbed to sludge. Consequently, antibiotic-resistant bacteria (ARB), including multiple-antibiotic resistant bacteria, have been detected in UWTPs.…”
Section: Introductionmentioning
confidence: 99%
“…Among the major point sources of environmental contamination from antibiotics are the UWTPs known for their low efficiency in removing such contaminants by the CAS process. 17 For example, Lindberg et al 18 reported that ciprofloxacin is not readily biodegradable in wastewater during CAS treatment and that 70% of its total amount is adsorbed to sludge. Consequently, antibiotic-resistant bacteria (ARB), including multiple-antibiotic resistant bacteria, have been detected in UWTPs.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the extensive application and wide-spectrum use of ABs in recent decades, AB residues are now frequently being detected in raw or treated wastewater (WW) [7][8][9] , hospital effluents 2,10,11 , surface water 2,[12][13][14] , groundwater 15,16 , and soil sediments in the natural systems 6,17 . The range of concentration is from ng L −1 (norfloxacin, 11.1-964 ng L −1 ) 8 to mg L −1 (ciprofloxacin, 28-31 mg L −1 ) 18 . Owing to the reality that ABs can cause severe damage to the aquatic and human life even in trace concentrations, their buildup in the environment and way up to the trophic levels has been recognized as one of the gravest environmental issues to policymakers and industry personnel worldwide 16 .…”
Section: Introductionmentioning
confidence: 99%
“…The higher residual concentrations of SAs were found in hospital and pharmaceutical wastewater [7]. Sulfisoxazole was found to reach 157.7 ng/L in wastewater treatment plants (WWTP) influent, and sulfadiazine in WWTP effluent reached 960 ng/L in China [8–9]. Sulfamethazine was not detected in airborne particulate matter collected near dairy production facilities [10], but it was found in dust samples collected from a pig‐fattening farm in Germany [11].…”
Section: Introductionmentioning
confidence: 99%